2012
DOI: 10.1080/03235408.2012.676818
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fungicide combinations, phosphoric acid and plant extract from stinging nettle on potato late blight management and tuber yield

Abstract: Late blight caused by Phytophthora infestans is a major constraint to potato production. Inadequate control of the disease has often resulted in potato yield losses. We assessed the efficacy of fungicides, phosphoric acid and stinging nettle extract combinations for late blight control at two locations in Kenya. Disease severity, relative area under disease progress curves (RAUDPC), pathogen lesions and tuber yield were quantified during the 2008 and 2009 cropping cycles. The application of metalaxyl alternate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Our present finding showed that the combination of resveratrol and pyrimethanil significantly inhibited the conidia germination and mycelial growth, and this is of particular significance as it prevents the further dissemination of B. cinerea . The findings of this study clearly demonstrated that two-drug combination will help to suppress the development of pathogen, which consistent with previous study focused on the combination of plant extracts and fungicides to control several plant pathogens, including Phytophthora infestans [ 43 ], Cercospora beticola [ 44 ], Uncinula necator [ 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our present finding showed that the combination of resveratrol and pyrimethanil significantly inhibited the conidia germination and mycelial growth, and this is of particular significance as it prevents the further dissemination of B. cinerea . The findings of this study clearly demonstrated that two-drug combination will help to suppress the development of pathogen, which consistent with previous study focused on the combination of plant extracts and fungicides to control several plant pathogens, including Phytophthora infestans [ 43 ], Cercospora beticola [ 44 ], Uncinula necator [ 45 ].…”
Section: Discussionsupporting
confidence: 91%